Drag, lift and torque correlations for non-spherical particles from Stokes limit to high Reynolds numbers. (September 2018) - Sanjeevi, Sathish K.P.; Kuipers, J.A.M.; Padding, Johan T.
Highlights: Hydrodynamic drag, lift and torque correlations for non-spherical particles. Three types of axisymmetric non-spherical particles are investigated. Correlations take into account expected physics at low and high Reynolds number. Correlations are valid in a larger range of Reynolds numbers than previous works. Abstract: Accurate direct numerical simulations are performed to determine the drag, lift and torque coefficients of non-spherical particles. The numerical simulations are performed using the lattice Boltzmann method with multi-relaxation time. The motivation for this work is the need for accurate drag, lift and torque correlations for high Re regimes, which are encountered in Euler-Lagrangian simulations of fluidization and pneumatic conveying of larger non-spherical particles. The simulations are performed in the Reynolds number range 0.1 ≤ Re ≤ 2000 for different incident angles ϕ . Different tests are performed to analyse the influence of grid resolution and confinement effects for different Re . The measured drag, lift and torque coefficients are utilized to derive accurate correlations for specific non-spherical particle shapes, which can be used in unresolved simulations. The functional forms for the correlations are chosen to agree with the expected physics at Stokes flow as well as the observed leveling off of the drag coefficient at high Re flows. Therefore the fits can be extended to regimes outside the Re regimes simulated. We observe sine-squared scaling of the drag coefficient for the particles tested even at R e = 2000 with C D, ϕ = C D, ϕ = 0 ∘ + ( C D, ϕ = 90 ∘ − C D, ϕ = 0 ∘ ) sin 2 ϕ . Furthermore, we also observe that the lift coefficient approximately scales as C L, ϕ = ( C D, ϕ = 90 ∘ − C D, ϕ = 0 ∘ ) sin ϕ cos ϕ for the elongated particles. The current work would greatly improve the accuracy of Euler-Lagrangian simulations of larger non-spherical particles considering the existing literature is mainly limited to steady flow regimes and lower Re .